Persepsi Guru PJOK Dan Guru Kelas Terhadap Peran Pendidikan Jasmani Dalam Mencegah Kekerasan Di Lingkungan Sekolah Dasar - Rani Nur’aeni; Chalifa Chairunnisa; Desti Rahmasari; Herna Aulia; Ghaida Putri Adella; Adam Firman Ferdiansah; Rahmat Permana (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Violence in the elementary school environment has a significant impact on the psychological, social, and academic development of students. This study aims to describe the perceptions of Physical Education, Sports and Health (PJOK) teachers and classroom teachers regarding the role of physical education in preventing violence in elementary schools. A combination of descriptive quantitative and qualitative methods was applied, with a sample of 6 teachers (3 physical education teachers and 3 class teachers) from SDN Liunggunung, Tasikmalaya. The participants were selected using proportional stratified random sampling to ensure representativeness. Data collection techniques included a 4-point Likert scale questionnaire, which was validated through expert judgment and tested for reliability using Cronbach’s Alpha (≥ 0.70), along with in-depth interviews to gain richer insights. The results revealed a consensus among both groups of teachers that physical education has a positive and strategic role in preventing violence. This is achieved through the internalization of core character values such as sportsmanship, cooperation, empathy, and discipline. Additionally, physical education serves as a medium to channel students’ physical energy into constructive activities and foster emotional regulation. Structured physical activities—such as team-based games, rhythmic gymnastics, and cooperative challenges—can reduce tendencies toward aggressive behavior and promote social interaction, inclusion, and mutual respect. However, the study also found significant challenges, including inadequate sports infrastructure, limited time allocation within the school curriculum, and the need for professional development among teachers. The conclusion emphasizes that physical education is a vital component in building a safe, inclusive, and character-driven school climate, but its success depends on consistent institutional support and ongoing teacher empowerment.